2016
DOI: 10.1007/s10551-016-3237-0
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Whistleblowing Studies: A Critical Review and Research Agenda

Abstract: Whistleblowing is a controversial yet socially significant topic of interest due to its impact on employees, organizations, and society at large. The purpose of this paper is to integrate knowledge of whistleblowing with theoretical advancements in the broader domain of business ethics to propose a novel approach to research and practice engaged in this complex phenomenon. The paper offers a conceptual framework, i.e., the wheel of whistleblowing, that is developed to portray the different features of whistleb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
165
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(201 citation statements)
references
References 119 publications
9
165
1
8
Order By: Relevance
“…The whistleblowing literature makes a general distinction between internal (i.e., reporting to someone within the firm) and external (i.e., reporting to someone outside the firm) whistleblowing (Dworkin and Baucus ; Sinzdak ; Park and Blenkinsopp ). The literature (e.g., Culiberg and Mihelič ) has also introduced another distinction: individuals who work inside the organization and report wrongdoing are “inside” whistleblowers. Conversely, people who disclose wrongdoing but are not part of the organization where it occurs are “outside” whistleblowers.…”
Section: Research Approach and Methodsmentioning
confidence: 99%
“…The whistleblowing literature makes a general distinction between internal (i.e., reporting to someone within the firm) and external (i.e., reporting to someone outside the firm) whistleblowing (Dworkin and Baucus ; Sinzdak ; Park and Blenkinsopp ). The literature (e.g., Culiberg and Mihelič ) has also introduced another distinction: individuals who work inside the organization and report wrongdoing are “inside” whistleblowers. Conversely, people who disclose wrongdoing but are not part of the organization where it occurs are “outside” whistleblowers.…”
Section: Research Approach and Methodsmentioning
confidence: 99%
“…The term 'member' is not explicitly defined, but it has generally been taken to mean organisational members or employees. 33 This excludes many individuals who may have links with an organisation and be in a position to observe, and raise concerns about, wrongdoing within the organisation. Miceli et al 34 note that many significant 'whistleblowing' cases reported in the press are technically not examples of whistleblowing, as the person who raised the concerns was not a current or former member of the organisation in question.…”
Section: Subjective -Objectivementioning
confidence: 99%
“…Although we acknowledge the logic of this attempt to bring definitional clarity to this new offshoot of the whistleblowing field, it is difficult for academics to impose such definitional precision retrospectively, once a term is out in the public domain and being used 'wrongly'. Culiberg and Mihelic 33 suggest that rather than framing the issue in terms of whistleblowing versus bell-ringing, it might be more useful to refer to insider versus outsider whistleblowing.…”
Section: Subjective -Objectivementioning
confidence: 99%
“…permanent vs. temporary appointments) and gender. These power elements have been identified as key factors in most commercial organisations' studies on organisational integrity (Dozier and Miceli 1985;Cassematis and Wortley 2013;Culiberg and Mihelic 2017). We also study the influence of the specific type of misconduct, i.e.…”
Section: Introductionmentioning
confidence: 99%